Staging Expertise in Times of COVID-19: An Analysis of the Science-Policy-Society Interface in the Dutch “Intelligent Lockdown” - Prettner, Robert; te Molder, Hedwig; Hajer, Maarten A.; Vliegenthart, Rens (Frontiers in Communication, 2021)
The corona crisis of 2020 took many by surprise. Quite suddenly, politicians had to make drastic decisions to guarantee public health, affecting basic civil liberties. In justifying their decisions, politicians internationally reverted back to a direct staging of experts to legitimize their proposals for what internationally became known as the “lockdown”. In this article we analyze the performance of the Dutch government that, early on, labeled its approach to COVID-19 as an “intelligent lockdown”. Our analysis examines the dramaturgy of expertise during this period. We selected two interrelated “stages”: the official press conferences, fully controlled by the government, and the responses on Twitter, as focal channel for critique from the general public, but also from opposition parties and (alleged) experts. 26 press conferences of the Dutch Prime Minister were analyzed and a search for the most popular posts on Twitter referring to the press conference(s) was carried out covering the period between March 6th and May 29th, 2020. The results show that the technocratic framing of expertise remained stable during the sampling period, regarding the undisputed status of expertise as the clear-cut basis for decision-making in uncertain times. Framing on Twitter challenged the omnipotence of the experts advising the government in various ways, namely, by referring to dissenting opinions of other experts, by questioning the underlying motives of experts’ advice or by pointing out that the policies were clearly contrary to everyday experience. We argue that it is not so much the facts themselves that are at stake here but hidden moralities, which include the government’s alleged complacency while asking citizens to blindly trust, its unpredictable behavior in the light of the promised straight line between scientific evidence and policy making, and its motivated behavior while claiming that the facts speak for themselves.